Antimicrobial potential of Streptomyces sp. to the Gram positive and Gram negative pathogens - Mysoon Al-Ansari; Noorah Alkubaisi; P. Vijayaragavan; K. Murugan (Elsevier, 2019)
Background: The occurrence of drug resistant infectious disease causing microbial pathogens was highly spreaded because of the wide level application of the commercially available antimicrobial agents. However, the eradication of the microbial pathogens was of huge demand. Although, many antimicrobial compounds were commercially available in the market however the spreading of the pathogens were hugely increased. Actinomycetes produce various secondary metabolites against pathogenic bacteria and fungi. The present investigation aimed to study the antimicrobial potential of the Streptomyces sp. towards infectious diseases causing pathogens. Methods: Culture dependable isolation techniques were followed for the isolation of the active actinomycetes isolates and the antimicrobial properties of the actinomcyetes were detected by primary screening techniques using modified starch casein agar medium. The active isolate was confirmed by various biochemical and morphological techniques. Results: In this study, 10 actinomycetes were isolated and later five were selected for secondary screening and noted significant activity against Enterobacter aerogenes and Proteus mirabilis. Among the selected Streptomyces sp., ES2 showed potent activity against selected microbes and was identified as Streptomyces sp. The studied isolates were resisitant towards streptomycin (10 μg), ampicillin (50 μg) and ciprofloxacin (5 μg). The organic solvent extracts of the promising isolate ES2 prononunced comparatively better inhibitory properties towards the studied pathogenic bacteria. Conclusion: Overall, the present study evidenced that the actinomycetes were promising candidate for the eradication of the pathogenic strains. Keywords: Actinomycetes, Microbial pathogens, Antimicrobial activity, Infectious diseases